1839 Ala. Acts 67, § 1 - (:unkn) unknown (General Publisher, 1839)
Prohibited the concealed carrying of “any species of firearms, or any bowie knife, Arkansas toothpick, or any other knife of the like kind, dirk, or any other deadly weapon.” Punished by a fine of $50-100 and imprisonment not to exceed 3 months.
Keywords: CARRY